Comparative plasma pharmacokinetics, tissue distribution and efficacy of two formulations ciprofloxacin-based in mouse - Breda, Susana Andrea (2009)
The aim of this study was to assess the plasma pharmacokinetics, tissue distribution and efficacy of a formulation ciprofloxacin (CIP)-Aluminum complex based (CIP-Al) in comparison with a conventional CIP formulation. For this study 96 Balb-C mice were divided in two groups and treated as follows: Group I received orally a single dose of CIP 5 mg/kg. Animals of Group II were identically treated but with CIP-AL formulation. Samples of blood, lung, intestine and kidney, were taken over 12 h post-treatment, and frozen until analysis by HPLC. The experimental efficacy study was based in an experimental Salmonella infection model in mice. Mice were divided into 3 groups: Control (distilled water treatment), CIP and CIP-Al. After 5 days of treatment survival was recorded. The plasma pharmacokinetics study outcomes revealed similar AUC values for CIP and CIP-Al. However, CIP concentration levels were statistically (P< 0.05) higher in lung, intestine and kidney after CIP-Al administration than those obtained for CIP conventional formulation group after 1h post treatment. The higher tissue concentrations of CIP-Al may have contributed to the observed efficacy trend where survived 33% of mice treated compared with the conventional CIP formulation assayed (0%). This fact would be related to the improved aqueous compatibility of CIP after aluminum complexation. We found that CIP-Al is at least as effective as CIP and exhibited advantageous pharmacokinetic and dispositional properties. It may become a valuable asset based on its formulation versatility due to higher solubility.